2019
DOI: 10.3390/ijerph16183296
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Distribution and Ecological Risk of Bisphenol Analogues in the Surface Water from a Water Diversion Project in Nanjing, China

Abstract: Due to the widespread use of bisphenol analogues (BPs) as alternatives to bisphenol A (BPA), considerable attention for health risk has been shown in aquatic ecosystems. The occurrence and distribution of six BPs were researched in a soluble phase (<10−3 μm), colloidal phase (10−3 μm to 1 µm), and suspended particulate matter (SPM >1 µm) in a water diversion project of Nanjing, China. Except for bisphenol Z, all BPs were detected in two or three phases, where the total concentrations of detected BPs were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 31 publications
(51 reference statements)
0
6
1
Order By: Relevance
“…As two of the main alternatives of BPA, BPF and BPS did not show significant existence in this study. The mean concentration of BPF in raw water was only at a slightly higher level than the maximum from Hangzhou Bay (3.50 ng L −1 ) in 2012 and the lower from Yangtze River (4.76 ng L −1 ) in 2019, 23,35 but much lower than the other studies. 36–39 The mean concentration of BPS in raw water from this study (0.61 ng L −1 ) was at the lowest level compared to other studies, e.g.…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…As two of the main alternatives of BPA, BPF and BPS did not show significant existence in this study. The mean concentration of BPF in raw water was only at a slightly higher level than the maximum from Hangzhou Bay (3.50 ng L −1 ) in 2012 and the lower from Yangtze River (4.76 ng L −1 ) in 2019, 23,35 but much lower than the other studies. 36–39 The mean concentration of BPS in raw water from this study (0.61 ng L −1 ) was at the lowest level compared to other studies, e.g.…”
Section: Resultscontrasting
confidence: 64%
“…The concentration level of BPE in this study (1.60–8.51 ng L −1 ) fell into the range of Yangtze River (N.D. – 2.12 ng L −1 ) in 2019 and Qinhuai River (N.D. – 50.0 ng L −1 ) in 2016. 35,43 The mean concentration of BPP was slightly higher than those reported in the Pearl River Delta in 2017 and 2020. 25,44 To the best of our knowledge, BPP was detected for the first time in the water bodies of the Taihu Lake Basin (0.260–4.93 ng L −1 ).…”
Section: Resultsmentioning
confidence: 78%
“…In the downstream, the detected concentrations of pharmaceuticals decreased along the river. The decreased concentrations may be attributed to the dilution effect or adsorption on the particulate matter and colloid in water [ 24 ], which would further settle into the sediment along the river. In addition, a previous study suggested that the abiotic or biotic processes in rivers, such as photolysis or microbial degradation, could also enhance the concentrations of metabolites downstream from parent degradation [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we can conclude that the developed method calibrated in MQ gives adequately accurate and precise results without the need for sample fortication. Even though the EPA 539 method recommends running a fortied sample with each analysis batch, it seems that in the literature this is usually not the case 10,23,24,32 as the standard addition principle is very time consuming. Similar to our methodology, in most methods in the literature, the SA principle is used solely to conrm that the method calibration is adequate in different matrices and is not used in routine analysis.…”
Section: Methods Validationmentioning
confidence: 99%
“…Analytical methods related to the occurrence of bisphenols are more numerous (more than 20 studies), and were performed with SPE extraction using sample volumes up to 2 L 10,32 and liquid–liquid extraction (LLE) with volumes up to only 20 mL. 33,34 All the mentioned studies utilized LC-MS/MS for analysis.…”
Section: Introductionmentioning
confidence: 99%